Tinjauan Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan Dalam Kepastian Hukum Poligami di Indonesia - mohamad Faisal aulia (ASIAN PUBLISHER, 2023)
This study aims to determine the legal certainty of polygamy in Law Number 1 of 1974 concerning Marriage in Indonesia. This research uses the Pustaka research method (field research). This research is descriptive normative, namely how to approach the problem under study based on the norms contained in laws relating to the legal certainty of polygamy. Data collection techniques include observation and interviews. The data analysis uses inductive and deductive techniques. The results in this study show that Law Number 1 of 1974 concerning Marriage has a requirement of a regulation, namely having legal certainty. This law has regulated how a man under certain conditions can have more than one wife. Criticism of gender injustice by making reproductive reasons as the basis for a man to be able to marry more than 1 person is also a living law that must be accommodated in regulations. The pros and cons of community living law related to polygamy must be addressed wisely by the regulators (DPR) so that the middle way can be accepted by all parties, such as eliminating the reason for sitri more than 1 person in psal 4 paragraph (2) of Law Number 1 of 1974 concerning Marriage, and directly to article 5